Enhancing health and eHealth literacy among nurses working with older people during COVID-19 pandemic: A multi-center e-Delphi study in five countries - Efthymiou, Areti; Evripidou, Melina; Karanikola, Maria; Menikou, Joanna; Tsitsi, Theologia; Efstathiou, George; Zeleníková, Renáta; Doležel, Jakub; Modrezejewska, Daria; Velonaki, Venetia Sofia; Kalokairinou, Athina; Papastavrou, Evridiki (My University, 2023)
Background: Nurses’ health literacy (HL) and ehealth literacy (eHL) knowledge and skills are crucial for patient care. There is evidence that skills and knowledge on how HL and eHL can facilitate the provision of care, is low among nurses. Especially in the care of older adults with an increased risk of falls and infections, or poor adherence to pharmacotherapy, nurses could increase patient safety by assessing and supporting older people’ HL and eHL. This study aims to present the findings of an e-Delphi survey, which was implemented within the framework of the development of a course focusing on the enhancement of HL and eHL assessment and intervention competencies for nurses. Method: A modified e-Delphi study was conducted in five countries from September 2020 to January 2021. Initially, a 19-item questionnaire on HL and eHL skills and competencies was developed by the research team based on literature review. Twenty experts from five countries (Cyprus, Czech Republic, Greece, Lithuania, Poland) participated in two e-Delphi rounds. The research team met to reach consensus on the final version of the modules. Results: Four modules were derived from the Delphi survey: 1) Introduction to HL and eHL 2) Communication skills in practice 3) eHealth challenges: Feasibility and readability issues, and 4) HL/eHL and patient safety. Conclusions: Raising awareness on HL and eHL skills in nurses and nursing students is considered a priority, especially during the COVID-19 era. The common effort among five academic institutions to develop an HL and eHL course targeting nurses and nursing students is considered an important step towards this direction.